2006
DOI: 10.1021/la0533720
|View full text |Cite
|
Sign up to set email alerts
|

Two-Compartment Micellar Assemblies Obtained via Aqueous Self-Organization of Synthetic Polymer Building Blocks

Abstract: We synthesized a symmetric linear ABCBA pentablock copolymer consisting of poly(ethylene oxide), poly(gamma-benzyl l-glutamate), and a poly(perfluoro ether) (fluorolink). The different blocks are highly immiscible with each other and form two-compartment micelles of mainly cylindrical shape in aqueous solution with lengths in the range of 100 to 200 nm and diameters of about 24 nm. The poly(perfluoro ether) (C blocks) forms the liquidlike center of the micelles (d = 6 nm). This is surrounded by a first shell o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
1
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 88 publications
(134 citation statements)
references
References 21 publications
3
129
1
1
Order By: Relevance
“…Thünemann and co-workers [24] observed cylindrical multicompartment micelles formed from ABC block copolymers consisting of hydrophilic poly(N-acylethyleneimine) endcapped with a hydrophobic fluorocarbon and a hydrocarbon block. They [25] also found that two compartment micellar solutions containing both spherical and cylindrical micelles could be formed from symmetric linear ABCBA pentablock copolymers consisting of poly(ethylene oxide), poly(g-benzyl L-glutamate) and poly(perfluoro ether)(fluorolink). Some typical morphologies observed are shown in Figure 1.…”
Section: Experimental Progress On Multicompartment Micellesmentioning
confidence: 99%
See 3 more Smart Citations
“…Thünemann and co-workers [24] observed cylindrical multicompartment micelles formed from ABC block copolymers consisting of hydrophilic poly(N-acylethyleneimine) endcapped with a hydrophobic fluorocarbon and a hydrocarbon block. They [25] also found that two compartment micellar solutions containing both spherical and cylindrical micelles could be formed from symmetric linear ABCBA pentablock copolymers consisting of poly(ethylene oxide), poly(g-benzyl L-glutamate) and poly(perfluoro ether)(fluorolink). Some typical morphologies observed are shown in Figure 1.…”
Section: Experimental Progress On Multicompartment Micellesmentioning
confidence: 99%
“…[15][16][17][18][19][20] At the moment, most work has focused on the preparation and characterization of new multicompartment micelles, [21][22][23][24][25] and an initial effort on the storage of two agents in a multicompartment micelle has recently been made. [26] Due to their structural complexity, it is difficult to assess the structure of the core of a multicompartment micelle rigorously, or indeed to visualize the evolution process of a multicompartment micelle directly by experiment.…”
Section: Feature Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Laschewsky et al 10 explored "spheres on spheres" multicompartment micelles formed from linear ABC block copolymers. Thünemann et al, 12 on the other hand, observed two-compartment cylindrical micelles formed from ABCBA block copolymers in dilute aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%